Factors Influencing the Adoption of Conservation Tillage Technology in Haru District, Oromia Regional State, Ethiopia (International Journal of Food and Nutritional Sciences, 2022)
The study determines the status and factors affecting adoption of conservation of technology in Haru district, Oromia regional state, Ethiopia. A multistage sampling technique was used to select 144 sample households from four PA’s. Descriptive statistics such as mean, standard deviations and frequencies were used to summarize the data while binary logit model were fitted to identify the most important variables influencing CT adoption decision behavior of sample households. Binary logit model indicated that frequency of contact with extension agent, frequency of participation in CT training, and frequency of participation in CT field days, education and social participation were found to have positive and significant influence on adoption of conservation tillage technology. Generally conservation tillage has economical and environmental benefit. This calls for the integration of policy makers, researchers, extension worker and farmers in planning, implementation, monitoring and evaluation. Therefore, the linkage of all actors to promote CT is a crucial for the present and future generation.